Model PKN Berbasis Proyek Kearifan Lokal untuk Meningkatkan Partisipasi Sosial Siswa Sekolah Dasar - Bherrio Dwi Saputra; Irfan Adi Nugroho; Eka Ridha Nofrida (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to develop and implement a project-based civic education model integrated with local wisdom to improve elementary students’ social participation. The background of this study stems from the lack of student engagement in Civic Education (PKn), which is often taught in a theoretical and non-contextual manner. This study employs a mixed-method approach using classroom action research in a fourth-grade class at a public elementary school. Data were collected through observation, interviews, questionnaires, documentation, and learning outcome tests. The findings indicate that project-based learning activities rooted in local values such as cooperation, mutual respect, and environmental care significantly enhanced students' social awareness and active participation in school and community life. Students were more engaged, collaborative, and empathetic. The results suggest that integrating local cultural values within project-based learning provides meaningful experiences that support the goals of Civic Education. This model can serve as an alternative instructional strategy aligned with the Merdeka Curriculum and the Profile of Pancasila Students framework.